Flexible Pedagogy, Flexible Teachers: Insights from a workshop-based inquiry - Thyrre Sørensen, Mia; Stenalt, Maria Hvid (Proceedings of the International Conference on Networked Learning, 2026)
Flexibility in Higher Education is increasingly framed as a necessary response to a complex and rapidly changing world, where students must adapt to shifting demands and conditions. Often associated with online and distance learning, flexibility is linked to increased accessibility, learner autonomy, and responsiveness to individual needs. The COVID-19 pandemic further accelerated the push for flexible educational models, exposing both the potential and the limitations of existing structures and practices. Despite its widespread use, flexibility remains a multifaceted and under-theorised concept, encompassing both pedagogical potential and structural challenges. It reflects a range of interpretations and priorities from institutional strategies shaped by market demands and technological innovation to pedagogical and personal approaches that focus on fostering student agency, critical thinking, and adaptability. This paper investigates how university teachers and researchers understand and construct the meaning of flexibility within the context of regular degree programs at a Danish university. Through two workshops involving approximately 35 participants, three artefacts - a flexibility barometer, a personal entry point, and a relationship matrix - were developed to facilitate reflection and dialogue. These artefacts supported conversations at multiple levels, ranging from grounded discussions grounded in participants’ own teaching practices to more open-ended, exploratory dialogues about flexibility as a pedagogical and institutional phenomenon. The analysis shows that flexibility is not merely a matter of logistics or technology, but rather a relational and context-dependent practice negotiated among teachers, students, and institutional structures. Participants highlighted both opportunities and dilemmas associated with flexible approaches, including the balance between structure and freedom, short-term responsiveness and long-term educational value, and tensions between individual autonomy and collective responsibility. Based on this, ten interrelated elements are identified through which flexibility is enacted, spanning timing, location, facilitation, student investment, and organisational infrastructure Rather than reinforcing dominant narratives that present flexibility as inherently positive or easily implemented, this study challenges such assumptions by revealing the situated negotiations, pedagogical considerations, and institutional constraints involved in enacting flexibility. The workshop dialogues revealed how teachers engage with flexibility through critical reflection, drawing on their professional experience and values. The study emphasises the importance of involving teachers in shaping flexible practices. Their insights and pedagogical perspectives are essential to ensuring that flexibility supports meaningful learning and aligns with broader educational goals.